Green Purchase Behavior: the Predictive Roles of Consumer Self-Determination, Perceived Customer Effectiveness and Perceived Price - Amenuvor, Fortune Edem; Owusu-Antwi, Kwasi; Bae, Seong-Chan; Shin, Sean Kwan Soo; Basilisco, Richard (International Journal of Scientific Research and Management (IJSRM), 2019)
The overarching aim of this research is to empirically test the effect of customers’ self-determined needs on perceived customer effectiveness and green purchase behavior while assessing the moderating role of price. To achieve this aim, data is collected from 453 consumers in South Korea. The various hypotheses developed to achieve this aim are tested via the structural equations modeling technique. The results of the study reveal that autonomy, competence, and relatedness positively and significantly affect perceived customer effectiveness. Additionally, autonomy and competence positively and significantly influence green purchase behavior. The study further finds that relatedness is negative but significantly related to green purchase behavior. Moreover, the study reveals that perceived customer effectiveness is positive and significantly related to green purchase behavior. Similarly, the study finds support for the moderating effect of price on the relationship between perceived customer effectiveness and green purchase behavior. The current study provides managerial and theoretical insights into understanding green purchase behavior, self-determined needs as well as perceived customer effectiveness.